Measuring the electronic properties of poly-si thin film solar cells deposited on textured substrate - Muhida, Riza; Sutjipto, Agus Geter Edy; Matsui, T.; Toyama, T.; Okamoto, H. (2006)
Electrical properties of PECVD produced poly-Si photovoltaic layers on the various textured substrates showing the light trapping effect have been investigated using an AC-conductivity technique. From temperature dependence of electron (hole) conductivities using n-i-n (p-i-p) structures, the Fermi level of the poly-Si layer on the slightly textured substrates is found to locate at the center of the band gap and this material is 'truly' intrinsic. As RMS roughness of the textured substrate, q increases, the Fermi level becomes close to conduction band edge, and finally, the poly-Si layer on the highly textured substrate exhibits n-type character even though any deposition conditions for the poly-Si layers are not changed at all. Changes in electrical conductivities of the poly-Si thin films in conjunction with the results on photovoltaic performances and microstructure are also discussed.